Enigmatic presence of rhyzoconcretion in Haliday Island in the Sundarbans, India: Geochemical insight - Supriyo Kumar Das; Dev Verma; Priyank Pravin Patel; Abhijeet Tripathi; Mainak Dutta; Dibyashree Mahapatra; Pravat Kumar Behera; Kaushik Gangopadhyay; Suchandra Mukherjee; Pankaj Kumar; Aritra Banerjee; Animesh Sinha; et al. (CATENA, 2026)

Edwardsiella ictaluri infection in farmed striped catfish Pangasianodon hypophthalmus in India - Chandra Bhushan Kumar; Tamal Seth; Devarshi Ranjan; Dev Kumar Verma; Naresh Kumar Sood; Neeraj Sood; Pravata Kumar Pradhan; Joykrushna Jena (Veterinary Research Communications, 2026)

Identification, Characterization and Expression Analysis of Calmodulin and Calmodulin-Like Protein Genes with Emphasis on Reproductive Organs of Chickpea (Cicer arietinum L.) - Avnika Verma; Vivek Dogra; Bharti Shree; Surender Singh Chandel; Harsh Nayyar; Rajeev Rathour; Kamal Dev Sharma (Plant Molecular Biology Reporter, 2026)

Cheilanthenetetraol, a sesterterpenoid isolated from Aleuritopteris bicolor with anti-hepatocellular carcinoma and anti-inflammatory activity - Kishan Singh; Smriti Verma; Rida Siddiqui; Monazza Israr; Dnyaneshwar Umrao Bawankule; Madhav Nilakanth Mugale; Kapil Dev (Journal of Natural Medicines, 2026)

Baicalein isolated from Oroxylum indicum acts as a potent µ- and κ-opioid receptor antagonist agent via the reversal of agonist-mediated cAMP inhibition - Kishan Singh; Anubhav Yadav; Sana Khan; Arti Shukla; Maksood Alam; Ashutosh Kumar Verma; Neerja Tiwari; Feroz Khan; Prem Narayan Yadav; Kapil Dev (Natural Product Research, 2025)

Widespread occurrence of Tilapia parvovirus in farmed Nile tilapia Oreochromis niloticus from India - Kooloth Valappil Rajendran; Neeraj Sood; B. Madhusudhana Rao; Anisha Valsalam; Megha K. Bedekar; Kezhedath Jeena; Pravata Kumar Pradhan; Anutosh Paria; Thangaraj Raja Swaminathan; Dev Kumar Verma; Naresh Kumar Sood (Journal of Fish Diseases, 2025)
Tilapia parvovirus (TiPV) has been associated with heavy mortalities in tilapia as a single infection or in co‐infection with Tilapia lake virus (TiLV). In this study, TiPV was detected in farmed Nile tilapia, Oreochromis niloticus , from two geographical regions of India, Maharashtra and Uttar Pradesh. TiPV‐specific polymerase chain reaction (PCR) reported earlier was used in the screening. Tilapia collected from Maharashtra showed characteristic clinical signs, and TiPV was detected along with TiLV and/or Aeromonas spp. However, fish from Uttar Pradesh were apparently healthy and only TiPV could be detected in these samples. A high prevalence of TiPV was recorded from both the geographical locations, Maharashtra and Uttar Pradesh (59.6% and 95.0% respectively). The virus could be detected in tissues such as the spleen, liver, kidney, brain and mucus. The spleen appeared to be the best tissue for detecting TiPV in apparently healthy tilapia. The presence of TiPV was further confirmed through sequencing the PCR products, isolation of the virus in the cell line and electron microscopy. Sequences of the NS1 gene of the two TiPV isolates showed similarity to the earlier reported TiPV isolates. The virus could be successfully propagated in O. niloticus Liver (OnL) cell line, and cytopathic effect was observed as early as 3 days post‐infection. Furthermore, the presence of non‐enveloped icosahedral to round virus particles measuring about 26–35 nm could be demonstrated in the cytoplasm and nucleus of infected OnL cells in transmission electron microscopy. With this confirmation of the presence of the virus, India is the third country to report TiPV after China and Thailand. The detection of TiPV in co‐infection cases with TiLV and in apparently healthy Nile tilapia suggests its wide distribution and potential synergistic effect in co‐infection cases. Therefore, this emerging virus needs holistic attention to understand its virulence, host‐specificity and epidemiological risk factors.

Establishment of a continuous cell line from heart of three spot gourami, Trichopodus trichopterus, a commercially important ornamental fish and its susceptibility to viruses - Aakriti Rastogi; Thangaraj Raja Swaminathan; Dev Kumar Verma; Hemant Kumar; Anutosh Paria; Pravata Kumar Pradhan; Uttam Kumar Sarkar; Neeraj Sood (Aquaculture, 2025)

A human machine interface (HMI) assisted portable device for measuring soil efflux using low-cost sensors: design, development and field evaluation - Tarandeep Singh; Aseem Verma; Manjeet Singh; Narendra Dev Patel; Gurmeet Singh Dheri; Kiranjeet Singh; Arshdeep Singh (Clean Technologies and Environmental Policy, 2025)

Cost-effective synthesis route for ultra-high purity of Ti3AlC2 MAX phase with enhanced performance of Ti3C2Tx MXene and MXene/NiO composite for supercapacitor application - Kapil Dev Verma; Kamal K. Kar (Chemical Engineering Journal, 2025)

Digital hemispherical photographs and Sentinel-2 multi-spectral imagery for mapping leaf area index at regional scale over a tropical deciduous forest - Mukunda Dev Behera; J. S. R. Krishna; Somnath Paramanik; Shubham Kumar; Soumit K. Behera; Sonik Anto; Shiv Naresh Singh; Anil Kumar Verma; Saroj K. Barik; Manas Ranjan Mohanta; Sudam Charan Sahu; Chockalingam Jeganathan; et al. (Tropical Ecology, 2024)

Susceptibility of selected tropical non-tilapine ornamental cichlids to Tilapia tilapinevirus following experimental infection - Anutosh Paria; Shrish C. Yadav; Dev Kumar Verma; Anup Mishra; Aakriti Rastogi; Ravindra; T.R. Swaminathan; K.V. Rajendran; Neeraj Sood; P.K. Pradhan (Aquaculture, 2023)

Phylogenetic analysis of Melolontha and Polyphylla beetles (Scarabaeidae: Coleoptera) from north-western Himalaya, India - Abhishek Rana; Ravinder Singh Chandel; Kamal Dev Sharma; Surender Singh Chandel; Kuldeep Singh Verma (Phytoparasitica, 2022)

Carps, Catla catla, Cirrhinus mrigala and Hypophthalmichthys molitrix Are Resistant to Experimental Infection with Tilapia Lake Virus (TiLV) - Pravata Pradhan; Dev Verma; Shrish Yadav; Atul Dev; Thangaraj Swaminathan; Anutosh Paria; Rajendran Valappil; Neeraj Sood (Fishes, 2021)
Tilapia tilapinevirus, also known as tilapia lake virus (TiLV), is an emerging fish virus that primarily affects tilapines. However, the virus has also been detected in a few non-tilapines. As tilapia is generally farmed in polyculture systems along with carps in South Asian countries, there is a likelihood that TiLV-infected tilapia can transmit the virus to the co-cultured species. In view of the above, the susceptibility of three carp species, namely catla (Catla catla), mrigal (Cirrhinus mrigala) and silver carp (Hypophthalmichthys molitrix) was evaluated vis-à-vis tilapia, following experimental infection with TiLV. No clinical signs and histopathological alterations could be observed in carps. RT-qPCR revealed that TiLV copy numbers in liver and brain of all the three carps were almost negligible and did not show any increase with time, suggesting that the virus did not replicate in liver and brain, the target organs of TiLV. Further, TiLV could not be isolated from pooled liver and brain tissues of carps using permissive CFF cell line. On the contrary, in tilapia, typical clinical signs and histopathological lesions were observed and there was significant increase in TiLV copy number up to 6 days post-injection. Furthermore, the virus was successfully isolated from pooled liver and brain tissue of infected tilapia. From the above findings, it could be concluded that C. catla, C. mrigala and H. molitrix are resistant to TiLV infection and unlikely to be carriers for this virus.

B-Map: a fuzzy-based model to detect foreign objects in a brain - Dev Baloni; Shashi Kant Verma (Medical & Biological Engineering & Computing, 2021)

Phytocompounds of Rheum emodi, Thymus serpyllum, and Artemisia annua Inhibit Spike Protein of SARS-CoV-2 Binding to ACE2 Receptor: In Silico Approach - Rajan Rolta; Deeksha Salaria; PremPrakash Sharma; Bhanu Sharma; Vikas Kumar; Brijesh Rathi; Mansi Verma; Anuradha Sourirajan; David J. Baumler; Kamal Dev (Current Pharmacology Reports, 2021)

Polyphasic characterization of and genomic insights into a haloalkali-tolerant Saccharibacillus alkalitolerans sp. nov., that produces three cellulase isozymes and several antimicrobial compounds - Himanshu Darji; Neha Verma; Yogita Lugani; Priyam Mehrotra; Dev Kant Sindhu; Venkata Ramana Vemuluri (Antonie van Leeuwenhoek, 2021)

Candidatus Actinochlamydia pangasiae sp. nov. (Chlamydiales, Actinochlamydiaceae), a bacterium associated with epitheliocystis in Pangasianodon hypophthalmus - N Sood; P K Pradhan; D K Verma; M K Yadav; Ravindra; A K Dev; T R Swaminathan; N K Sood (Journal of Fish Diseases, 2018)
Chlamydial infections are recognised as causative agent of epitheliocystis, reported from over 90 fish species. In the present study, the farmed striped catfish Pangasianodon hypophthalmus (14–15 cm, 70–90 g) with a history of cumulative mortality of about 23% during June and July 2015, were brought to the laboratory. The histopathological examination of gills from the affected fish revealed presence of granular basophilic intracellular inclusions, mostly at the base of the interlamellar region and in gill filaments. A concurrent infection with Trichodina spp., Ichthyobodo spp. and Dactylogyrus spp. was observed in the gills. The presence of chlamydial DNA in the gills of affected fish was confirmed by amplification and sequencing of 16S rRNA gene. BLAST ‐n analysis of these amplicons revealed maximum similarity (96%) with Candidatus Actinochlamydia clariae. On the basis of phylogenetic analysis, it was inferred that the epitheliocystis agents from striped catfish were novel and belonged to the taxon Ca . Actinochlamydia. It is proposed that epitheliocystis agents from striped catfish will be named as Ca . Actinochlamydia pangasiae. The 16S rRNA gene amplicons from novel chlamydiae were labelled and linked to inclusions by in situ hybridisation. This is the first report of epitheliocystis from India in a new fish host P. hypophthalmus .

An In Silico Approach for Identification of the Pathogenic Species, Helicobacter pylori and Its Relatives - Ayush Puri; Arshiya Rai; P. S. Dhanaraj; Rup Lal; Dev Dutt Patel; Anju Kaicker; Mansi Verma (Indian Journal of Microbiology, 2016)